Updated notes on the interindustry wage structure, 1890-1990. - Allen, Steven G. (Industrial & Labor Relations Review, 1995)
The author documents and analyzes changes in wage structures across manufacturing industries over the years 1890-1990. Interindustry differentials in wages were highly stable over that period for production workers, but much less stable for nonproduction workers. Interindustry wage patterns were very similar for production and nonproduction workers in 1990, though this similarity dates back only to 1958. Although dispersion of wages across industries followed varying trends over the period, it was higher in 1990 than at any previous time in this century. The variables that have been most strongly correlated with wage growth are productivity growth, rising union density, rising capital intensity, and profit growth. Reprinted by permission of the publisher.